The Women Neuroscientists in the Cajal School - Elena Giné; Carmen Martínez; Carmen Sanz; Cristina Nombela; Cristina Nombela; Fernando de Castro (Frontiers Media S.A., 2019)
At the beginning of the 20th century, in view of the growing international recognition of Santiago Ramón y Cajal, the Spanish authorities took some important steps to support Cajal's scientific work. This recognition peaked in 1906, when Camillo Golgi and Santiago Ramón y Cajal shared the Nobel Prize in Physiology or Medicine. The Spanish government provided Cajal a state-of-the-art laboratory in Madrid to allow him to continue with his research and they funded salaries to pay his first tenured collaborators, the number of which increased further after the creation of the Junta para Ampliación de Estudios (JAE). The JAE was an organism set up to help promising researchers develop their careers in different ways, thereby contributing to the development of science in Spain. Although largely forgotten or relatively unknown, there has been a recent revival in the recognition of the school that developed around Cajal, collectively referred to as the Spanish Neurological School (or colloquially, as the Cajal School or School of Madrid). Almost all Cajal's collaborators were men, although a limited number of female scientists spent part of their careers at the heart of the Cajal School. Here we discuss these women and their work in the laboratory in Madrid. We have tracked the careers of Laura Forster (from Australia/United Kingdom), Manuela Serra, María Soledad Ruiz-Capillas and María Luisa Herreros (all Spanish), through their scientific publications, both in the journal founded by Cajal and elsewhere, and from other documentary sources. To complete the picture, we also outline the careers of other secondary figures that contributed to the production and running of Cajal's laboratory in Madrid. We show here that the dawn of Spanish neuroscience included a number of contributions from female researchers who to date, have received little recognition.